Analysis of Single Punching Forging Press Setup by Using ANSYS - Rajmane, Umesh C.; Nagaraj, A. M. (Asian Journal of Science and Applied Technology, 2016)
The proposed work is concern to study single punching forging press setup by carrying out analysis and stress distribution on die. To Analysis of stress distribution on base plate. Experimental system is to be developed to achieve the stated objective which includes mainly at examining the deformation and stresses on all main parts of the forging press setup The main feature of press is forging. A forging is produced by the downward stroke of the ram when the punch moves towards and into the die block set.